PENGARUH UKURAN PERUSAHAAN DAN DEBT TO EQUITY RATIO (DER) TERHADAP AUDIT DELAY PADA PERUSAHAAN SEKTOR BARANG KONSUMEN PRIMER YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dewi, Susana; Gunawan, Sulthan (Universitas La Tansa Mashiro, 2023)
Financial reports are one of the most important tools to support the sustainability of a company, because they play a role in measuring and assessing a company's performance. Delay in financial reporting has a negative impact on the reaction of capital market participants. There are still companies that are late in providing or submitting their financial reports to the Financial Services Authority (OJK). Audit Delay is the length of time for completion as measured from the closing date of the book to the date of issuance of the financial statements. This study aims to determine: (1) The effect of company size on audit delay, (2) The effect of solvency on audit delay, (3) The effect of company size and solvency on audit delay in primary consumer goods sector companies listed on the Indonesia Stock Exchange (IDX). ) period 2017-2021. The sample for this research is primary consumer goods sector companies for the 2017-2021 period using a purposive sampling method. From a population of 105 companies, there are 51 companies that meet the criteria as a research sample. The data processing analysis tool in this study used SPSS version 25. The results showed that company size had a significant effect on audit delay, debt to equity ratio (DER) had a significant effect on audit delay, company size and debt to equity ratio (DER) had a significant effect on audit delays.